Remote skin self‐examination training of melanoma survivors and their skin check partners: A randomized trial and comparison with in‐person training - June K. Robinson; Racheal Reavy; Kimberly A. Mallett; Rob Turrisi (Cancer Medicine)
Abstract Background Compared with other cancers, melanoma has the longest delays measured as the median time to patient presentation for care from symptom onset. Time to presentation for care is a key determinant of outcomes, including disease stage, prognosis, and treatment. Methods Melanoma survivors with localized disease and their skin check partners enrolled in two sequential randomized control trials of skin self‐examination (SSE) training. In Phase 1, the pair read a workbook in the office and had quarterly total body skin examinations with a study dermatologist. In Phase 2, materials were mailed to pairs, whose surveillance was with a community physician. SSE knowledge, performance (frequency and extent), and identification of concerning moles were compared between phases. Results Among 341 patients, 197 received the workbook and the others were controls. Knowledge in performing SSE was higher for the workbook relative to controls in both phases. The SSE frequency ranged from 2.38 to 5.97 times in 9 months. Patients randomized to the workbook in both phases performed significantly more SSE than controls at 9 months (P < .05). In both phases, trained survivors performed significantly more SSEs on the scalp than controls at 9 and 18 months (P < .05). Phase 1 survivors performed significantly more SSEs on the abdomen, buttocks, and soles of the feet than controls, but this did not occur in Phase 2. Finally, in both phases, survivors trained with the workbook resulted in greater detection of suspicious lesions and melanomas. Conclusions These findings justify the benefits of remote SSE training for patients as an adjunct to provider‐administered screening.